When the show must go on: Investigating repeated organizational change in elite sport - Wagstaff, C. R. D.; Gilmore, S.; Thelwell, R. C. (Journal of change management, 2016)
This study responded to recent calls for the investigation of employees responses to repeated organizational change events. Data were gathered via 20 semi-structured interviews with 10 employees from 2 organizations competing in English football `s Barclays Premier League. The results indicated that employees responded to recurring organizational change in positive and negative emotional, behavioural, and attitudinal ways. The main positive response themes related to: re ilience, learning, performance, challenge appraisals, and autonomy. The main negative response themes related to: trust, cynicism, organizational development, motivation, turnover, engagement, and commitment. The findings illustrate the value of exploring and monitoring employee responses to both single and repeated organizational change. Specifically, the data indicate increasingly deteriorating employee attitudes across change events, but also highlight the important role of cognitive appraisal for responses to each change event. The results are discussed in regard to implications for organizational change research and practice in dynamic contexts such as elite sport